Gamma Ray Spectroscopy for Logging While Drilling in Mineral Exploration - Hooshyari Far, Ida (Curtin University, 2018)
Natural gamma ray spectroscopy has changed little in 30 years. Simulations, laboratory scale models, and field experiments all demonstrate that the natural gamma ray spectrum recorded during borehole drilling can be used to track changes in heavy element concentrations with the Heavy Mineral Index, and it correlates well with iron-rich zones. This research creates a basis for a new generation of safe logging-while-drilling tools plus changes the analysis of airborne radiometrics in the future.